2023
DOI: 10.3390/biom13081178
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface B2m-Free Human Leukocyte Antigen (HLA) Monomers and Dimers: Are They Neo-HLA Class and Proto-HLA?

Abstract: Cell surface HLA-I molecules (Face-1) consist of a polypeptide heavy chain (HC) with two groove domains (G domain) and one constant domain (C-domain) as well as a light chain, B2-microglobulin (B2m). However, HCs can also independently emerge unfolded on the cell surface without peptides as B2m-free HC monomers (Face-2), B2m-free HC homodimers (Face 3), and B2m-free HC heterodimers (Face-4). The transport of these HLA variants from ER to the cell surface was confirmed by antiviral antibiotics that arrest the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 199 publications
0
3
0
Order By: Relevance
“…These monomers expressed on cells both in tissues and in circulating exosomes expose cryptic epitopes masked by B2M when they are intact. Such exposure induces immune recognition and production of antibodies not only against allele-specific HLA monomers but also epitopes shared by all HLAs [29]. Our adapted MAIPA is not capable of detecting these types of HLA antibodies, MEM-G9 binding only to non-denatured HLA-G monomers or dimers.…”
Section: Discussionmentioning
confidence: 95%
“…These monomers expressed on cells both in tissues and in circulating exosomes expose cryptic epitopes masked by B2M when they are intact. Such exposure induces immune recognition and production of antibodies not only against allele-specific HLA monomers but also epitopes shared by all HLAs [29]. Our adapted MAIPA is not capable of detecting these types of HLA antibodies, MEM-G9 binding only to non-denatured HLA-G monomers or dimers.…”
Section: Discussionmentioning
confidence: 95%
“…B2M mutations are known to occur with varying frequencies in various tumor types and some tumors like bladder cancer are known to downregulate B2M in the absence of hard mutations within the gene [3]. Downregulation of B2M is generally believed to facilitate escape of tumors from immunosurveillance and immune-mediated destruction Downregulation of B2M is generally believed to facilitate escape of tumors from immunosurveillance and immune-mediated destruction [4] our results underscore that loss of B2M and HLA-A expression is specific to tumor cells but in the majority of cases it is not permanent and can be upregulated through immunotherapy treatment [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The polyreactivity of several HLA-specific mAbs came to light when they were tested with a Luminex multiplex beadset coated with at least 90 different HLA molecules. For example, the widely used anti-HLA-E mAb MEM-E/02 (Affinity Bioreagents, Golden, CO, USA) was employed to immunolocalize HLA-E on 19 different human cancer tissues (see Table 2 in [4]). The HLA-I reactivity of two different lots of MEM E/02 [5] was examined using dual-laser flowcytometric Luminex xMAP multiplex bead technology, and it demonstrated that MEM-EM/02 reacted with several HLA-B and HLA-C alleles in addition to HLA-E.…”
Section: Introductionmentioning
confidence: 99%